Development of Learning Media Android based for Increase Quality SMK OTKP Learning with ADDIE Model - Hazar, Siti; Firdaus, Rangga (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
Improving the quality of education in Vocational High Schools (SMK) is a strategic challenge in responding to the growing needs of the industrial world, especially in the Office Automation and Governance (OTKP) department. One solution that can be applied is the development of technology-based learning media, such as Android applications, to increase learner engagement and understanding. This study aims to develop and test the effectiveness of Android-based learning media using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) at SMK OTKP Way Kanan. The research used the Research and Development (R&D) method with qualitative and quantitative approaches. Data were collected through interviews, observations, and questionnaires. The results of material expert validation obtained an average score of 87.5% (very feasible category), and the results of media expert validation obtained a score of 85% (very feasible category). The small group trial showed an increase in the average score from 68.4 to 83.7, while the large group trial showed an increase from 66.2 to 85.1. The results of interviews and observations support these findings, showing an increase in enthusiasm, active participation, and student understanding of the material. Thus, the Android-based learning media developed proved effective in improving the quality of learning and can be used as a model for the development of similar media in other departments and levels in vocational education.